Asimov: A Remote Laboratory for Experimentation in Educational Robotics - Maruyama, Gustavo Yoshio; Castro Junior, Amaury Antônio De; Lima, Anderson Corrêa De; Vilhanueva, Marcos Pinheiro (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This paper discusses the development overview, testing, and evaluation of the Asimov - Remote Robotics Laboratory system. It is a remote experimentation environment that allows people, anywhere in the world, to conduct practical programming experiments on robots or microcontrolled devices remotely. The system was practically tested through the implementation of a basic programming and robotics course, delivered entirely online in an asynchronous format, with the practical component conducted through the developed system. Finally, a usability evaluation of the system was performed based on user perceptions of its usefulness, ease of use, graphical interface, and educational value.